Crowded trades, market clustering, and price instability - Marc van Kralingen; Diego Garlaschelli; Karolina Scholtus; Iman van Lelyveld (Tinbergen Institute, 2020)
Crowded trades by similarly trading peers influence the dynamics of asset prices, possibly creating systemic risk. We propose a market clustering measure using granular trading data. For each stock the clustering measure captures the degree of trading overlap among any two investors in that stock. We investigate the effect of crowded trades on stock price stability and show that market clustering has a causal effect on the properties of the tails of the stock return distribution, particularly the positive tail, even after controlling for commonly considered risk drivers. Reduced investor pool diversity could thus negatively affect stock price stability.
Keywords: G02; G14; G20; 330; crowded trading; tail-risk; financial stability